2004
DOI: 10.1063/1.1759062
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pulse duration on the amorphization of GeSb thin films under ultrashort laser pulses

Abstract: Ab initio calculations on structural, elastic and dynamic stability of CdO at high pressures J. Appl. Phys. 112, 093523 (2012) 1,1-diamino-2,2-dinitroethylene under high pressure-temperature J. Chem. Phys. 137, 174304 (2012) Topological phase transition and unexpected mass acquisition of Dirac fermion in TlBi(S1−xSex)2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
(18 reference statements)
2
13
0
Order By: Relevance
“…5 Over past decades, binary alloys such as GeTe and Sb 2 Te 3 and ternary alloys, located along the GeTe-Sb 2 Te 3 pseudobinary line, were intensively studied both theoretically 6 and experimentally in relation to their applications in optical phase-change data storage. These studies explored a vast number of parameters including pulse duration, 7 wavelength, 8 pulse energies, 9 the role of oxygen impurities, 10 vacancies, 11 and local structure. 12 Time-resolved optical studies using ps and fs laser pulses have already revealed important details of the phase transition, such as the existence of three distinct stages, namely, rapid melting, solidification, and slow relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…5 Over past decades, binary alloys such as GeTe and Sb 2 Te 3 and ternary alloys, located along the GeTe-Sb 2 Te 3 pseudobinary line, were intensively studied both theoretically 6 and experimentally in relation to their applications in optical phase-change data storage. These studies explored a vast number of parameters including pulse duration, 7 wavelength, 8 pulse energies, 9 the role of oxygen impurities, 10 vacancies, 11 and local structure. 12 Time-resolved optical studies using ps and fs laser pulses have already revealed important details of the phase transition, such as the existence of three distinct stages, namely, rapid melting, solidification, and slow relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pulse duration of the femtosecond laser is much shorter than the thermal diffusion time, which results in incomplete re-distribution of the absorbed laser energy in both the horizontal and vertical directions. The ultra-short pulse duration deposits the energy to heat up the sample in less than one hundred femtoseconds (10 À13 s) with a rapid cooling rate (Wiggins et al 2004). Such a steep temperature gradient makes it difficult for heat to dissipate to the surrounding area and thus confines the heat inside a much smaller area of the phase change film to produce these nano-sized features.…”
Section: Methodsmentioning
confidence: 99%
“…This research has largely concentrated on Sbrich films. [7][8][9][10][11][12] It was shown that cycling between the crystalline and amorphous phases of 25-nm-thick GeSb films induced by single laser pulses of duration of 100 fs or 20 ps is achieved in the 400-800 nm wavelength range. 11 The phase transformation dynamics of GeSb materials upon picosecond and femtosecond laser-pulse excitations was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] It was shown that cycling between the crystalline and amorphous phases of 25-nm-thick GeSb films induced by single laser pulses of duration of 100 fs or 20 ps is achieved in the 400-800 nm wavelength range. 11 The phase transformation dynamics of GeSb materials upon picosecond and femtosecond laser-pulse excitations was investigated. [10][11] The shortest transformation times have been reported and induced by 30 ps pulses at 583 nm in 25-nmthick Sb-rich GeSb films on glass substrates where the complete a ↔ c crystallization transformation times were as low as ∼ 400 ps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation